The Role of Inhibitory Receptors in Monosodium Urate Crystal-Induced Inflammation - Fernandes, Maria J.; Naccache, Paul H. (Frontiers in Immunology, 2018)
Inhibitory receptors are key regulators of immune responses. Aberrant inhibitory receptor function can either lead to an exacerbated or defective immune response. Several regulatory mechanisms involved in the inflammatory reaction induced by monosodium urate crystals (MSU) during acute gout have been identified. One of these mechanisms involves inhibitory receptors. The engagement of the inhibitory receptors Clec12A and SIRL-1 has opposing effects on the responses of neutrophils to MSU. We review the general concepts of inhibitory receptor biology and apply them to understand and compare the modulation of MSU-induced inflammation by Clec12A and SIRL-1. We also discuss gaps in our knowledge of the contribution of inhibitory receptors to the pathogenesis of gout and propose future avenues of research.